Quantitative Research of 11C-CFT and 18F-FDG PET in Parkinson’s Disease: A Pilot Study With NeuroQ Software - Sun, Xun; Liu, Fang; Liu, Qingyao; Gai, Yongkang; Ruan, Weiwei; Wimalarathne, Dilani Neranjana; Hu, Fan; Tan, Xubo; Lan, Xiaoli (Frontiers in Neuroscience, 2019)
Objectives Dopamine transporter (DAT) and glucose metabolism imaging have been applied in the diagnosis of Parkinson disease (PD). We explored the possibility of evaluating for PD with NeuroQ software by analyzing 11C-2β-carbomethoxy-3β-(4-fluorophenyl) tropane (11C-CFT) and 18F-FDG PET/CT. Methods We retrospectively analyzed brain 11C-CFT and 18F-FDG PET/CT of 38 patients with parkinsonism, including 20 PD, 10 multiple system atrophy (MSA) and 8 essential tremor (ET), and compared them with the PET/CT of 11 normal healthy controls (NC). PD patients were divided into mild and moderate-severe grade according to the Hoehn-Yahr (H&Y) scale. The 11C-CFT uptake in the caudate nuclei (CN) and putamen (Pu) normalized with cerebellum (CN/Cb and Pu/Cb) were obtained with a manual method and NeuroQ software, and their diagnostic performance were compared. 18F-FDG uptake of specific regions were also obtained with NeuroQ, and the enhancement effect for the differential diagnosis was evaluated. Results There was significant agreement between the manual method and NeuroQ method for 11C-CFT uptake by CN (r2=0.680) and Pu (r2=0.770). 11C-CFT uptake by CN and Pu in PD and MSA patients was significantly lower compared with NC and ET patients. The cutoffs of CN/Cb and Pu/Cb for the distinction between PD and NC were 1.71 and 2.20, respectively. No difference in uptake ratios occurred between PD and MSA. 18F-FDG uptake by the pons and cerebellum in the MSA group was markedly decreased. It was highly accurate in distinguishing between PD and MSA when combined with analysis of 11C-CFT uptake. Pu/Cb decreased significantly in mild grade PD compared to NC group (1.92±0.33 vs 2.82±0.43); however statistically significant decrease in CN/Cb wasn’t observed until the moderate-severe grade PD (1.43±0.11 vs 2.23±0.36). In early asymmetric PD, a statistically significant difference could be seen with Pu/Cb between the symptomatic and asymptomatic side (2.17 ± 0.30 vs 1.95 ± 0.22). Conclusions 11C-CFT and 18F-FDG PET/CT can be analyzed quantitatively with NeuroQ software, which provides an accurate method for the diagnosis and severity evaluation of PD.